Mafisa: Communion ecclesiology of Acts 2:42–47 in action - Resane, Kelebogile T. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2025)
The Batswana people practise a cultural tradition known as mafisa, which involves borrowing and lending as a way of poverty alleviation within the community. Its main purpose is to narrow the gap between the rich and the poor. Conversely, communion ecclesiology embodies the principle of giving, whereby believers respond to the needs of the poor so that none among them lacks. Both mafisa and communion ecclesiology centre on mutual giving as a way of overcoming economic hardship. The objective of this article is to demonstrate how mafisa and communion ecclesiology, expressed as koinonia, work in synergy to address poverty alleviation in communities. The study engages African cultural epistemology to highlight the community’s inherent capacity to uplift and emancipates itself from economic menaces. It further seeks to show that African epistemologies can be applied to understand theological epistemologies such as koinonia. Drawing on a literature study, the two entities are defined, analysed, and compared to reveal their role in addressing poverty. While mafisa represents a secular cultural practice and koinonia a spiritual theological concept, the two complement one another for a good course. The article concludes that the ecclesia of Acts 2:42–47 practised both mafisa and koinonia, serving the community to bridge the economic gap between the rich and the poor. Contribution: The decolonisation of theology can be advanced through African philosophies and community-driven initiatives aimed at addressing socio-economic devastations. Mafisa represents one such initiative and aligns with theological dictum known as communion ecclesiology. Together these two approaches contribute to poverty alleviation by applying Jesus’s principle that freely you have received, freely you must give. Those who are blessed will in turn bless others.